Prevalence of ESBL-producing Escherichia coli in adults with and without HIV presenting with urinary tract infections to primary care clinics in Zimbabwe. Issue 2 (30th June 2021) - Olaru, Ioana D; Ferrand, Rashida A; Chisenga, Mutsawashe; Yeung, Shunmay; Macrae, Bruce; Chonzi, Prosper; Stabler, Richard A; Hopkins, Heidi; Mabey, David; Masunda, Kudzai P E; Kranzer, Katharina
Abstract: Background: People living with HIV may be at increased risk for infections with resistant organisms. Infections with ESBL-producing organisms are of particular concern because they limit treatment options for severe Gram-negative infections in low-resource settings. Objectives: To investigate the association between HIV status and urinary tract infections (UTIs) with ESBL-producing Escherichia coli . Patients and methods: Cross-sectional study enrolling adults presenting with UTI symptoms to primary care clinics in Harare, Zimbabwe. Demographic and clinical data were collected during interviews and a urine sample was collected for culture from each participant. Antimicrobial susceptibility testing was performed according to EUCAST recommendations. Results: Of the 1164 who were enrolled into the study, 783 (64%) were female and 387 (33%) were HIV infected. The median age was 35.8 years. Urine cultures were positive in 338 (29.0%) participants, and the majority of bacterial isolates were E. coli ( n  =   254, 75.2%). The presence of ESBL was confirmed in 49/254 (19.3%) E. coli . Participants with HIV had a 2.13 (95% CI 1.05–4.32) higher odds of infection with ESBL-producing E. coli than individuals without HIV. Also, the prevalence of resistance to most antimicrobials was higher among participants with HIV. Conclusions: This study found an association between HIV and ESBL-producing E. coli in patients presenting with symptoms suggestive of UTI to primary care in Harare. HIV status should be considered when prescribing empirical antimicrobial treatment.